ISLAM IN THE WEST MEDIA DISTORTION (MEDIA IN CONSTRUCTING ISLAM AS A TERRORIST AND EXTREMIST RELIGION) - Ifah, Ifah (QAULAN: Journal of Islamic Communication, 2021)
Various media reports that directly or indirectly have formed public opinion that accuses Muslims as a whole as accused of all forms of violence and terrorism on the face of the earth accompanied by extremist acts. Some western media are trying to brainwash the global community that where there are Muslims then there are terrorists and where there are terrorists then there is a threat accompanied by extremist acts. This article aims to see how western media are constructing the message that Islam is the religion of terrorists and extremists. The method used is the study of literature. The results show that the Media has a big impact on a person's view of something and using only symbols of Islam, they can be accused of being terrorists. The media constructs messages in the form of writings or images that link terror acts with Muslims. Muslims, in general, are suspected of being part of terrorists, even for small neighborhoods. So it is clearly seen that the media is trying to form a negative concept of Islam as a religion of terrorists and extremists.